Radical combustion in two stroke engine / Abdul Rahim Abdul Rahman and Muhamad Suwaid Saad - Abdul Rahman, Abdul Rahim; Saad, Muhamad Suwaid (Faculty of Mechanical Engineering, 1998)
Stringent legislation concerning the pollution of atmosphere by engine exhaust gases have been tightened recently and hence placed an extensive pressure on engine manufacturers to meet these emission standards. Two-stroke engines are known for their high emission levels in particular unburnt HC and NOx. Different research and development programmes were initiated in order to eliminate this fundamental weakness of two-stroke engines. Hence a number of techniques have been studied and used to achieve improvements in fuel economy and emission levels of two-stroke engines. Most recently, the use of radical combustion process in two-stroke engines has been reported as a promising way to achieve these improvements. The hot residual gases excessively present in two-stroke engines seems to have a major role on the onset of abnormal combustion especially at light loads where there is excessive cyclic variation and irregular combustion. The variation of residual gas distribution at the vanicity of the spark plug due to improper local scavenging is the main factor that affect the initial period of combustion. The divergent effect of the residual gases on the abnormal and knocking combustion and the irregular combustion and misfiring are the most important aspects of combustion process in two-stroke engines A new combustion process initiated by the generation of a radicals from the previous combustion cycle could be of potential influence on the emission levels and fuel consumption of two-stroke engines. These radicals are used as local energy spots during the mixing process with the fresh charge. The establishment of such combustion process required a certain running conditions. These conditions included the amount of the residual gases to be trapped each cycle and recirculated to the next cycle, the mixing process of the fresh air-fuel charge and the residual gases to form a stratified mixture, the combustion chamber and piston geometry, the air-fuel ratio, the compression ratio, and the exhaust gases temperature.